1977
DOI: 10.1128/jb.130.3.1010-1016.1977
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-dependent inactivation of gramicidin S synthetase in Bacillus brevis

Abstract: Incorporation of L_[14C]ornithine into gramicidin S by crude, unfractionated lysozyme extracts of Bacillus brevis ATCC 9999 was shown to represent the activity of the gramicidin synthetase complex. Frozen-thawed cells were the source of active extracts, but when cells were shaken in air at 370C, they rapidly lost activity in a first-order reaction with a half-life of 13 min. Protease inhibitors and inhibitors of energy metabolism had no effect on the inactivation process in frozen-thawed cells. Stabilization w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1980
1980
1989
1989

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(2 citation statements)
references
References 29 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…The molecular mechanism of inactivation of the antibiotic synthetases is unknown. In vitro incubation of the heavy gramicidin S synthetase at 37°C for 1 h resulted in an 80% loss of gramicidin S-synthesizing activity (46,100). Kleinkauf and Koischwitz (101) reported that this inactivation was due to the presence of a protease in the crude extract; they also observed that the heavy enzyme was divided into subunits of different sizes by proteolytic enzymes and that this could be prevented by adding a mixture of protease inhibitors.…”
Section: Irreversible Decay Of Antibioticmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanism of inactivation of the antibiotic synthetases is unknown. In vitro incubation of the heavy gramicidin S synthetase at 37°C for 1 h resulted in an 80% loss of gramicidin S-synthesizing activity (46,100). Kleinkauf and Koischwitz (101) reported that this inactivation was due to the presence of a protease in the crude extract; they also observed that the heavy enzyme was divided into subunits of different sizes by proteolytic enzymes and that this could be prevented by adding a mixture of protease inhibitors.…”
Section: Irreversible Decay Of Antibioticmentioning
confidence: 99%
“…It is interesting to note that removal of oxygen in vivo by sparging with nitrogen prevents inactivation of gramicidin S synthetase (46,47). Oxygen is required for growth, but it is possible that control of dissolved oxygen, to provide a high degree of oxygen transfer during exponential growth followed by a moderate degree of oxygen transfer during the stationary phase, could improve antibiotic production.…”
Section: Irreversible Decay Of Antibioticmentioning
confidence: 99%